Blood pressure reduction induced by chronic intracerebroventricular or peroral clonidine administration in rats with salt-dependent or angiotensin II-dependent hypertension - Zicha, J; Řezáčová, L; Behuliak, M; Vaněčková, I (Physiological research, 2022)
The agonists of alpha(2)-adrenergic receptors such as clonidine, rilmenidine or monoxidine are known to lower blood pressure (BP) through a reduction of brain sympathetic outflow but their chronic antihypertensive effects in rats with low-renin or high-renin forms of experimental hypertension were not studied yet. Moreover, there is no comparison of mechanisms underlying BP reduction elicited by chronic peroral (po) or intracerebroventricular (icv) clonidine treatment. Male salt-sensitive Dahl rats fed 4% NaCl diet and Ren-2 transgenic rats were treated with clonidine administered either in the drinking fluid (0.5 mg/kg/day po) or as the infusion into lateral brain ventricle (0.1 mg/kg/day icv) for 4 weeks. Basal BP and the contributions of renin-angiotensin system (captopril 10 mg/kg iv) or sympathetic nervous system (pentolinium 5 mg/kg iv) to BP maintenance were determined in conscious cannulated rats at the end of the study. Both peroral and intracerebroventricular clonidine treatment lowered BP to the same extent in either rat model. However, in both models chronic clonidine treatment reduced sympathetic BP component only in rats treated intracerebroventricularly but not in perorally treated animals. In contrast, peroral clonidine treatment reduced angiotensin II-dependent vasoconstriction in Ren-2 transgenic rats, whereas it lowered residual blood pressure in Dahl rats. In conclusions, our results indicate different mechanisms of antihypertensive action of clonidine when administered centrally or systemically.
Keywords: kuchyňská sůl; renin; potkani transgenní; Hypertension; chlorid sodný; Angiotensin II; angiotensin II; krysa rodu Rattus; Antihypertensive Agents; sympatický nervový systém; Clonidine; zvířata; Rats, Transgenic; clonidin; Renin; Rats, Inbred Dahl; krevní tlak; Male; Sodium Chloride, Dietary; hypertenze; hypotenze; Rats; Animals; Sodium Chloride; Hypotension; mužské pohlaví; antihypertenziva; Sympathetic Nervous System; Blood Pressure; potkani inbrední Dahl